Controle de posição de uma plataforma plana para captação de radiação solar - Silva, Milton Medeiros da (2013)
This study aims at the design, development and performance evaluation of a flat platform to capture incident solar radiation. The design and implementation of a fuzzy system for the efficient control of the solar tracking movement of the platform are also presented